Abnormalities in the EEG power spectrum in bulimia nervosa, binge‐eating disorder, and obesity: A systematic review. (25th October 2018) - Blume, Marie; Schmidt, Ricarda; Hilbert, Anja
Abstract: To provide a basis for electroencephalography (EEG) neurofeedback protocols for bulimia nervosa (BN), binge‐eating disorder (BED), and obesity, this systematic review investigates alterations in EEG‐measured brain activity, specifically frequency bands. A systematic literature search with predefined search terms yielded N  = 7 studies meeting the inclusion criteria. The risk of bias was assessed for all studies. In resting‐state EEG, the beta activity was elevated in fronto‐central regions in individuals with obesity and co‐morbid BED. In food‐cue conditions, both obese individuals with and without BED showed increased beta activity, suggesting increased awareness of food cues and a heightened attentional focus towards food stimuli. The level of beta activity was positively correlated with eating disorder psychopathology in resting and food‐cue conditions. In individuals with BN, there was no evidence for altered EEG spectral power. The results indicate specific alterations in EEG‐based brain activity in individuals with BED and obesity. More high‐quality studies are needed to further confirm these findings and to transfer them into EEG‐based interventions.